(untitled) (Acta Scientiarum. Biological Sciences, 2022)
The present study describes the length-weight relationship of four species of ornamental fish caught on the banks of Tupé lake in lower Rio Negro, Amazonas state, Brazil in the months of September and December 2017, and February, March, and April 2018 with the aid of gillnets (20 m x 2 m, with 5 mm between knots), and landing nets, which were used specifically for collections close to the trunks. Acarichthys heckelii (b= 2.9444) and Nannostomus unifasciatus (b=3.0887) were the only species to show isometric growth, while Pseudoloricaria laeviuscula (b=3.273) showed positive allometric growth and Hemigrammus levis (b=2.5216) presented negative allometric growth. All length-weight-relationships presented herein are recorded for the first time from the Rio Negro basin